Internal marketing: reward system and its impact on employee performance in Sabah Cultural Board / Mohd Azizan Jamikah - Jamikah, Mohd Azizan (2015)
This research aims to determine the reward system and its impact on employee performance in Sabah Tourism Board. The reward system dimensions namely extrinsic and intrinsic which are the independent variable while dependent variable is the employee performance. The objective of this study. Each of the reward system dimensions was tested to see its relationship with the employee performances. The objective of this study are, to identify the elements of reward system influencing employee performance, to examine the relationship between elements of reward system towards employee performances and to examine the most significant reward system to increase the employee performance. Questionnaire were distribute to 108 respondents came from various background and all of them are employee in Sabah Cultural Board. Two hypothesis have been tested using statistical package for social science (SPSS) version 21.0. The findings indicated that intrinsic has the highest significant relationship to employee performances. The employee believes that the intrinsic reward are the most common factor that affects the employee performances. The implication of each variables and further suggestion for future research were identified and proposed.